2018
DOI: 10.1044/2018_jslhr-l-16-0432
|View full text |Cite
|
Sign up to set email alerts
|

The Receptive–Expressive Gap in English Narratives of Spanish–English Bilingual Children With and Without Language Impairment

Abstract: In early stages of L2 learning, bilingual children with PLI have an L2 receptive-expressive gap, but their typical development peers do not. Using a single picture during narrative generation might be advantageous for this population because it minimizes a receptive-expressive gap.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 51 publications
1
1
0
Order By: Relevance
“…Also in line with prior research of bilingual narrative development (Gibson et al, 2018), children performed significantly better on narrative comprehension (M = 6.17) than on narrative production (M = 4.46); thus, the main effect for mode was significant (F 1,12 = 21.27, p < .001) with a large effect size, η p 2 = .680. There also was a significant languageby-mode interaction (F 1,12 = 5.81, p = .037, η p 2 = .367).…”
Section: Topics In Language Disorders/october-december 2021supporting
confidence: 87%
“…Also in line with prior research of bilingual narrative development (Gibson et al, 2018), children performed significantly better on narrative comprehension (M = 6.17) than on narrative production (M = 4.46); thus, the main effect for mode was significant (F 1,12 = 21.27, p < .001) with a large effect size, η p 2 = .680. There also was a significant languageby-mode interaction (F 1,12 = 5.81, p = .037, η p 2 = .367).…”
Section: Topics In Language Disorders/october-december 2021supporting
confidence: 87%
“…Similarly, Trabasso et al (1992) found that English monolingual 4-year-olds, who did not spontaneously produce goals of story characters in their narratives, could give reasons why a character performed an action when explicitly probed. In a recent longitudinal study using the Test of Narrative Language (TNL; Gillam & Pearson, 2004), Gibson, Peña, and Bedore (2018) analysed English narratives from Spanish–English bilinguals with typical language development ( N = 20) and with language impairment ( N = 20) at age 6 and age 7. In the TNL story generation task with multiple pictures (the task most similar to the one used in the current study), the typically developing children performed consistently better in comprehension than in production across time points.…”
Section: Introductionmentioning
confidence: 99%